The critical role of bone density in implant dentistry: a review article - Raghavan, Rohit; P. A., Shajahan; Rajsree, B. M. (International Journal of Research in Medical Sciences, 2025)
Bone density is a crucial factor for the success of dental implants. A strong, dense jawbone provides the necessary foundation for the implant to fuse with the surrounding bone, a biological process called osseointegration. This direct connection between the implant and the bone is what makes it stable and ensures it lasts a long time. Without adequate bone density, which can be compromised by systemic conditions like osteoporosis or localized bone loss, the implant lacks a solid anchor. This can lead to poor primary stability, delayed healing, and a significantly higher risk of failure. To precisely assess this critical parameter, dentists rely on a classification system, such as the Misch classification, which categorizes bone quality into four distinct types, from D1 (dense cortical bone) to D4 (very fine trabecular bone). This detailed evaluation is essential as it directly informs the surgical procedure, guiding the clinician in selecting the optimal implant design and placement technique to ensure a predictable and successful outcome.